TOWARD AN INDONESIAN CURRENT IN ISLAMIC EXEGESIS: An Attempt to Contextualize the Maqasid al-Quran (JOURNAL OF INDONESIAN ISLAM, 2019)
The slogan that the al-Quran suits all time and space should not be just a rethoric. It should be proven in reality instead. As we live today, the distance has been very long from the time and space of the revelation of the al-Quran. This long time and spatial gap create gaps between the al-Quran and its readers. Therefore, there should be efforts to minimize the gaps by safeguarding the value and themes of the al-Quran. One of the important efforts is contextualization and revitalization of Quranic messages. This can be done by obtaining deep understanding of the al-Quran to uncover basic and universal message of the al-Quran which bridge time and space. The next step is to apply it led by principles of ulum al-Quran such as asbab al-nuzul and the concepts of Makkiyyah-Madaniyyah. This article not only focuses on reinterpretation of the al-Quran, but also applies the concept of contextualization of the Quranic messages under the slogan of the al-Quran suits all time and space. In addition, this article also exposes the contextualization of the al-Quran with the context of contemporary Indonesia through the reinterpretation of three concepts of ghanimah, jihad, and ‎polygamy.